Arabidopsis EIN3-binding F-box 1 and 2 form ubiquitin-protein ligases that repress ethylene action and promote growth by directing EIN3 degradation - Gagne, Jennifer M. (National Academy of Sciences, 2004)
Ubiquitination of various intracellular proteins by ubiquitin-protein ligases (or E3s) plays an essential role in eukaryotic cell regulation primarily through its ability to selectively target proteins for degradation by the 26S proteasome. Skp1, Cullin, F-box (SCF) complexes are one influential E3 class that use F-box proteins to deliver targets to a core ligase activity provided by the Skp1, Cullin, and Rbx1 subunits. Almost 700 F-box proteins can be found in Arabidopsis, indicating that SCF E3s likely play a pervasive role in plant physiology and development. Here, we describe the reverse genetic analysis of two F-box proteins, EBF1 and -2, that work coordinately in SCF complexes to repress ethylene action. Mutations in either gene cause hypersensitivity to exogenous ethylene and its precursor 1-aminocyclopropane-1-carboxylic acid. EBF1 and -2 interact directly with ethylene insensitive 3 (EIN3), a transcriptional regulator important for ethylene signaling. Levels of EIN3 are increased in mutants affecting either EBF1 or -2, suggesting that the corresponding SCF complexes work together in EIN3 breakdown. Surprisingly, double ebf1 ebf2 mutants display a substantial arrest of seedling growth and have elevated EIN3 levels, even in the absence of exogenous ethylene. Collectively, our results show that the SCF(EBF1/EBF2)-dependent ubiquitination and subsequent removal of EIN3 is critical not only for proper ethylene signaling but also for growth in plants.